Tanggung Gugat Pemerintah Atas Kebocoran Data Pribadi Masyarakat Dalam Perspektif Undang-Undang Pelindungan Data Pribadi - Syofyan, Yunita; Nazmi, Didi; Arfiani, Arfiani (Faculty of Law, Andalas University, 2025)
The development of digital technology can affect the performance of data management systems carried out by both government and private agencies, various digital-based activities that have an impact on efficiency in performance. Data leaks obtained through electronic media are valuable things such as population registration numbers, family cards, and identity cards. The importance of protecting personal data so that there is no data exploitation by irresponsible parties. The results of this study answer the problem, namely, first, the PDP Law has not been able to provide legal protection to citizens if the government as the data controller has been negligent over personal data. This, legal accountability for the government's negligence in protecting the personal data of its citizens still refers to government actions that are not in accordance with the general principles of good governance or abbreviated as AUPB as regulated in Law Number 30 of 2014 concerning Government Administration. Second, Legal Protection for the Community Experiencing Personal Data Leaks in Facebook account data leaks can be carried out through a State Administrative Dispute Lawsuit as based on Article 17 paragraph (1) and paragraph (2) letter c of Law Number 30 of 2014 concerning Government Administration in the form of abusing authority. The basis for the State Administrative Lawsuit against the Government is because the act of leaking data on Facebook accounts belonging to Indonesian citizens has violated the provisions of the General Principles of Good Governance (AUPB), especially accuracy, public interest, and good service as regulated in Article 2 of Law Number 30 of 2014 concerning Government Administration. However, the government can also be sued in a civil manner if there is negligence in controlling personal data belonging to citizens as regulated in Article 12 of Law Number 27 of 2022 concerning Personal Data Protection.